Analyzing Equitable Goods Distribution: Integrating Fair Division Principles and Game Theory - Zhang, Lei; Ni, Chenmin; Wang, Mengping; Tang, Lisha (International Journal of Global Economics and Management, 2024)
This research focuses on the equitable allocation of indivisible goods among five agents, where each agent holds goods contributing to its profit. The dual objectives are to maximize all agents' collective profit and ensure the fairness of goods distribution. Fair distribution is identified as a significant social challenge. The study aims to explore and elucidate the fair relationships within goods distribution through the lens of game theory, a methodological framework that has seen rapid advancements in various fields. Utilizing game theory for this analysis is crucial for advancing social equity and improving public satisfaction with distribution outcomes.